Prediction Model of 30-Days Postoperative Pneumonia in Elderly Patient Undergoing Abdominal Surgery - Dwimartutie, Noto; Oktadiana, Harini; Singh, Gurmeet; Jeo, Wifanto Saditya; Harimurti, Kuntjoro (UI Scholars Hub, 2022)
Introduction. Physiologic changes in respiratory tract in elderly increase incidence of post-operative pneumonia. Post-operative pneumonia in non-thoracic surgery was found higher in abdominal surgery. This study aimed to develop a prediction model of 30-day post-operative pneumonia in elderly patients undergoing abdominal surgery. Methods. A retrospective cohort study was conducted using elderly patient’s medical records who underwent abdominal surgery in Cipto Mangunkusumo General Hospital. Multivariate analysis using logistic regression was used to determine Odds Ratio (OR). Model’s calibration performance was determined by Hosmer-Lameshow test and its discrimination performance was determined by calculating area under the curve (AUC). Results. Of 753 subject who underwent abdominal surgery, postoperative pneumonia was found in 9.2% subjects. Independent predictors for 30-day postoperative pneumonia were functional status [ADL Barthel 0-11, odds ratio (OR) 6.908 (95% confidence interval (CI) 2.933-16.273); ADL Barthel 12-19, OR 3.191 (95%CI 1.53-6.657)], upper abdominal surgery [OR 4.869 (95%CI 1.805-13.132)], chronic obstructive pulmonary disease [OR 6.888 (95%CI 2.001-23.709)], and albumin level /dl [OR 2.54 (95%CI 1.404-4.596)]. Prediction model of pneumonia was stratified into lower risk (score 3; probabililty 60.42%). Hosmer-Lemeshow test revealed p-value 0.452 and the AUC value is 0.811 (95%CI 0.87-0.97). Conclusion. A simple prediction model of 30-day post-operative pneumonia for elderly patients undergoing abdominal surgery consisted of 4 predictors (functional status, upper abdominal surgery, COPD and albumin level /dl) has a good performance.